Responsive Constitutional Law Strategy For Preventing Political Corruption Done By Local Political Dynasties - Riwanto, Agus; Suryaningsih, Sukarni (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
This article aims to examine corruption practices in the regions carried out by political dynasties and prevention efforts from the perspective of responsive constitutional law. It will examine the motives of political dynasties, forms of corruption by dynasties, factors that cause dynasties and efforts to prevent. This article uses a socio-legal method that is an interdisciplinary approach in the study of law by combining social sciences or humanities. Secondary data mainly comes from case, regulations and library. The results of the study show that the dynasties tend to practice the forms of corruption in the regions: corruption in the buying and selling of regional government positions and corruption in regional infrastructure projects originating from the Regional Budget Revenue. Factors causing political dynasties: the high cost of regional head elections and the absence of laws prohibiting dynastic practices in regional head elections. Efforts to prevent the practice of political dynasties for regional head elections from the perspective of responsive constitutional law are in the form of policies to regulate the regional head election system that prioritizes the principle of responsibility for public demands and provides alternative solutions through: reducing the cost of regional head elections, lowering the threshold for candidacy, changing the financing of regional head elections from the Regional Revenue Expenditure Budget to the State Expenditure Budget, separating local and national elections, a political culture that educates the people in voting, and policies for the welfare of the people in order do not elect dynastic candidates in regional head elections.